Analisis Evaluasi Pendidikan Karakter Peserta Didik Dalam Manajemen Kurikulum 2013 Di Sekolah Pedesaan Dan Perkotaan - Deitje Adolfien Katuuk; Meytha Meyske Wongkar; Samuel Harry Mossey; Davison Pagawak (Journal on Education, 2024)
This research aims to analyze the evaluation of students' character education in the 2013 curriculum management in rural and urban schools. This research uses qualitative methods with library study techniques based on data all sourced from national journal databases. At the same time, appropriate search terms are a prerequisite for accurate data acquisition. To make search results as comprehensive and accurate as possible, the Authorb of Science core collection was selected for this study. This research uses the subject "2013 Curriculum Management and Character Education". The results of this research indicate that in order to improve the quality of learning in the 2013 Curriculum, teachers need to use student characteristics and culture as a basis for developing learning principles and programs. Because, whatever efforts are chosen and carried out by teachers and learning designers if they do not rely on the individual characteristics of students as learning subjects, the learning they develop will not be meaningful for students.